(untitled) (e-Journal of Linguistics, 2023)
This descriptive qualitative research on audiovisual translation aims to describe and analyze two elements, namely, the wordplay translation strategies applied by the translator in Scary Movie 3 and the effectiveness of the strategies from a multimodality perspective. Three instruments were used in collecting data; transcription sheet, selection sheet and category matrix. The result revealed that four strategies were implemented in translating wordplay in this movie: wordplay translation into non-wordplay, zero translation, wordplay translation by borrowing the wordplay of the source language, and wordplay translation to wordplay with a related rhetorical device. Furthermore, it was also found that the effectiveness of the strategies was supported by the existence of images (nonverbal visual channel (NVC)), background sounds (nonverbal auditory channel (NAC)), dialogue (verbal auditory channel (VAC)), and the subtitles (verbal-visual channel (VVC)). The holistic analysis of all polysemiotic channels in the scenes show that the characteristics of audiovisual translation does not align the monosemiotic translation. The existence of the semiotic channels allow the text compression in the subtitle without reducing the naration flow.